Une question archéologique syrienne. De l’archéologie comme symbole de notre destin - Michel al-Maqdissi (Les Cahiers d’EMAM)
Our archeology has changed considerably since the start of the civil war and the “question archéologique syrienne” is going through a delicate period where current predators are unable to envisage a future to rebuild an “archéologie de paix” capable of reconstructing the ancestral heritage of the country. Thus, our archeology becomes the symbol of a destiny assimilated into a chain of aggression, which leads us to build a catastrophic future.